Biosynthesis of Self-Dispersed Silver Colloidal Particles Using the Aqueous Extract of P. peruviana for Sensing dl-Alanine. (2nd February 2014) - Rashid, Mohd; Sabir, Suhail
Abstract : We report the biosynthesis of silver nanoparticles (AgNPs) in a single step using edible fruit aqueous extract of P. peruviana that essentially involved the concept of green chemistry. Yellowish-brown color appeared upon adding the broth of P. peruviana to aqueous solution of 1 mM AgNO3 which indicates the formation of AgNPs. The maximum synthesis of these nanoparticles was being achieved in nearly 2 hrs at 28°C. The synthesis of AgNPs was followed by AgNPs UV-visible spectroscopy. Particle size and morphology of AgNPs were studied by transmission electron microscopy (TEM) and scanning electron microscopy (SEM), respectively. These studies revealed that the AgNPs characterized were spherical in shape with diameter ranging from 31 to 52 nm. The energy dispersive X-ray spectroscopy showed that the AgNPs present are approximately 63.42 percent by weight in the colloidal dispersion. The absorption spectra of the AgNPs in absence and presence of dl -alanine show a distinguish shift in surface plasmon resonance (SPR) bands. Thus, these nanoparticles may be used as a chemical sensor for dl -alanine present in the human blood.